Early Drug Prescription Patterns as Predictors of Final Workers Compensation Claim Costs and Closure: An Updated Analysis on an Expanded Cohort. Issue 12 (19th December 2022) - Tao, Xuguang (Grant); Lavin, Robert A.; Yuspeh, Larry; Tsourmas, Nicholas F.; Kalia, Nimisha; Leung, Nina; Williams, Leila; Hunt, Dan L.; Green-McKenzie, Judith; Bernacki, Edward J.
Abstract : This study evaluated the early drug prescription patterns as predictors of final workers compensation claim costs and closure based on an updated analysis on a large cohort. The result would provide claim management with tools to estimate final claims outcomes in the first 3- or 6-months post-injury. Abstract : Objective: The aim of the study is to determine the associations of workers' compensation claim costs and return to work with drugs prescribed for early symptom management. Methods: Claims filed from 1998 to 2007 were followed for 10 years from the injury date. Drugs analyzed included gabapentin, pregabalin, antipsychotics, antidepressants, sedatives, benzodiazepines, carisoprodol, and opioids, controlling for initial reserve, sex, age, physical therapy, attorney involvement, and surgery. Results: Gabapentin, antipsychotics, antidepressants, and sedatives used in the first 3 months after injury were significantly associated with higher claim cost (≥$100, 000). All opioid morphine equivalent doses greater than or equal to 5 mg/d for the first 6 months was significantly associated with higher cost (≥$100, 000) and not being released to work at end of third year after injury with dose-response relationships. Conclusions: Prescription patterns in the first 3 months or first 6 months of workers' compensation claim development may be used as predictors of claim outcomes.